SISTEM INFORMASI PENDATAAN JEMAAT GKI MARTHEN LUTHER KAMPKEY - Cornelia Wasti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
GKI Marthen Luther Kampkey is one of the churches in the Port Numbay Class area. GKI Marthen Luther Kampkey has a congregation of 2,673 people divided into 7 districts. Every 6 months GKI Marthen Luther Kampkey conducts church data collection activities aimed at evaluating ministry, planning and implementing ministry programs, coaching and church development, which are then published in form of a church statistics book. However, the implementation of church data collection activities is still ineffective because errors often occur in recording or data collection because the data is input repeatedly every time the church data collection activities are carried out. Therefore, we need a church data collection information system that can store church data, easier to search church data and make data reporting. With the GKI Marthen Luther Kampkey congregational data information system, the GKI Marthen Luther Kampkey secretariat can easily store church data, register new church members, update member data, record church events, and report church data. This study uses the waterfall system development method with UML system design which is then tested with Blackbox Testing. The result of this research is a congregational data collection information system built using the PHP programming language and MySQL database.